2018
DOI: 10.5194/acp-18-4425-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of convective ice evaporation on interannual variability of tropical tropopause layer water vapor

Abstract: Water vapor interannual variability in the tropical tropopause layer (TTL) is investigated using satellite observations and model simulations. We break down the influences of the Brewer-Dobson circulation (BDC), the quasibiennial oscillation (QBO), and the tropospheric temperature ( T ) on TTL water vapor as a function of latitude and longitude using a two-dimensional multivariate linear regression. This allows us to examine the spatial distribution of the impact of each process on TTL water vapor. In agreemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 73 publications
10
41
1
Order By: Relevance
“…As a final caveat, we have focused mostly on the winter TWP during normal conditions. Our conclusions about the role of convection mostly describe that region and are not likely to apply to anomalous situations such as El Niño (Avery et al, ; Ye et al, ), to the summer TTL nor to saturated regions observed near the Asian monsoon. Indeed, Figure b suggests that in the summer months, convection in the Asian monsoon region is more closely tied to the highest RHi region consistent with the findings of Ueyama et al ().…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As a final caveat, we have focused mostly on the winter TWP during normal conditions. Our conclusions about the role of convection mostly describe that region and are not likely to apply to anomalous situations such as El Niño (Avery et al, ; Ye et al, ), to the summer TTL nor to saturated regions observed near the Asian monsoon. Indeed, Figure b suggests that in the summer months, convection in the Asian monsoon region is more closely tied to the highest RHi region consistent with the findings of Ueyama et al ().…”
Section: Discussionmentioning
confidence: 78%
“…It is well understood that convection is the primary source of water in the midtroposphere (Corti et al, 2006;Folkins et al, 2002;Minschwaner & Dessler, 2004;Romps, 2014) and convection is occasionally observed to detrain even above the tropopause (e.g., Avery et al, 2017;Corti et al, 2008;Kelly et al, 1993;Wang & Dessler, 2012). There is clear evidence that it is playing a role in the TTL's water vapor budget, both in direct measurements of water vapor (Schoeberl et al, 2018;Ye et al, 2018) and in other tracers, such as HDO (Dessler et al, 2007;Moyer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is the hydrating effect due to underestimating of total water when the laminar cirrus ice is not visible to the MLS. Note that this hydrating effect is different from those caused by the convectively lofted ice in current (Ye et al, ) and future climate (Dessler et al, ).…”
Section: Conclusion Remarksmentioning
confidence: 91%
“…This regression model is similar to the one used in Dessler et al (2013) and Ye et al (2018). Here, ΔT is the tropical average 500-hPa temperature anomaly in kelvin, which is superior to the El Niño-Southern Oscillation index, because it captures more subtle variability of clouds (see Figure 7a).…”
Section: Laminar Cirrus Frequencymentioning
confidence: 99%
“…Large interannual variations of water vapor in the tropical UTLMS have been observed and shown to be important for both climate and chemical reasons (e.g., Dessler et al, 2013;20 Fueglistaler and Haynes, 2005;Liang et al, 2011;Liess and Geller, 2012;Randel and Jensen, 2013;Tao et al, 2015;Ye et al, 2018). Several well-known interannual climate modes are found to modulate the interannual variations of tropical UTLMS water vapor, such as the El Nino Southern Oscillation (ENSO) (e.g., Dessler et al, 2014;Liang et al, 2011;Randel et al, Atmos.…”
mentioning
confidence: 99%